Checklist of the Freshwater Fishes of Argentina (CLOFFAR) - Mirande, Juan Marcos (2015)
The purpose of this paper is to present an updated list of freshwater fishes found in Argentina based on the available literature. Since the last list was published in 2003, most systematical and distributional changes were presented on www.pecescriollos.de and updates have been published frequently. In only 12 years the number of species reported from Argentina has increased from 379 to 515 and the mentioned accumulative updates at the end had reached 15 pages, becoming a little bit complex and cluttered when used as supplements to the list published by López et al. (2003). After receiving several incitements we finally decided to review the available data and elaborate the present contribution. As usual in the past years already, we will continue to frequently publish updates, offering the possibility to keep updated on the species of freshwater fishes from Argentina.